Clinical Analysis of 17 Cases of Borderline Ovarian Tumors During Pregnancy - Wang, Mingdan; Li, Yue; Xu, Tongtong; Shi, Chen; Jiang, Lili; Liu, Kuiran (Frontiers in Oncology, 2022)
Objective The study retrospectively analyzed the clinical characteristics and prognosis of 17 cases of pregnancy complicated by borderline ovarian tumors to provide help for clinical workers. Materials and Methods The clinicopathological data of 17 patients with ovarian borderline tumors during pregnancy at the Shengjing Hospital of China Medical University from January 2015 to June 2021 were collected and analyzed retrospectively. The average age of the patients was 31.82 years (25–45 years), the average number of pregnancies was 2.06 times (1–6 times), and the average number of births was 0.41 times (0–1 time). Results Among the 17 patients, 4 were diagnosed in the first trimester, 2 in the second trimester, and 11 in the third trimester. Most of the first symptoms were cysts, cyst enlargement, or cyst rupture. Among them, 3 cases (1 in the first trimester and 2 in the second trimester) continued pregnancy after a conservative operation, 9 cases underwent cesarean section and a conservative operation simultaneously, and the mother and child had a good outcome. Two cases underwent conservative operations and induced abortion, and 1 case underwent an ectopic pregnancy operation at the same time. The prognosis of the patients was good without recurrence. Conclusion Preoperative diagnosis of borderline ovarian tumors in pregnancy is delayed, and imaging and tumor markers are not specific. The coincidence rate between intraoperative frozen pathology and postoperative paraffin pathology was not high. Borderline tumors are mainly treated by surgery, and the prognosis for mothers and infants is good.